Investigating story of ( Sheikh San’an ) from a narratological perspective Based on "Gérard Genette"’ s theory - yadollah Shokri (مطالعات زبانی و بلاغی)
Study of the structure and form of literary works have provided a background for developing methods for growth of meaning in these texts . Tales and stories that contribute a huge part of world literature create different semantically methods and sciences with their structure .among these, narratology has created a new method in art and narrative literature arena by employing methods and principals for organizing and analyzing elements of the story .Theory of narratology in addition to attracting the attention of critics towards new methods of structural analysis has provided employment of these methods during narrative studies in the field of contemporary literature. "Gérard Genette" as one of the narratology theorists has proposed one of the most important issues of this science .He define narrative from the three levels of story, narrative and narration, with its components .The present article analyzes Sheikh Sanan story from the perspective of this theorist’s narratology .The results show that in this story levels of Genette’ s theory of narrative such as story narrative and narration and elements such as discipline, order, time duration, volume and tone exist in parts of the story and in some cases continue to narrate the story to the end with slightly different elements.